Chapter Massimo Quaini: geografia storica, fonti, conoscenze territoriali e loro uso politico e socio-culturale - Rombai, Leonardo (Territori, 2021)
Quaini's commitment is aimed - with the development of the Gambian concept - towards the construction of a critical and operational historical geography (usable for the aware and sustainable management, institutional planning and socio-cultural use of territories), through innovative theoretical-methodological reflections and concrete case studies: with a focus on the landscape-territorial historicity and the heritage of regions and places, and openness to interdisciplinarity and local knowledge, integrating - with exemplary critical contextualization - the written and graphic documentary sources with those of the terrain.